Impact of COVID-19-Related Distress on Anxiety and Depression of College Students - Jain Mathew; Preksha Yadav; Sridevi Nair; Roseline Gomes; Sheeba Bhaskar (Journal of Learning for Development, 2022)
The current study explores the impact of COVID-19 related distress factors on the mental well-being of college students. For the purpose of the study, mental well-being is measured through the depression symptoms and general anxiety levels of the students. The study used judgemental sampling to identify the respondents of the study. The final sample consisted of 147 respondents and the data was analysed on SPSS. The results suggested that while COVID-19 distress factors were not significant in predicting the level of depression symptoms experienced by the students, the general anxiety levels were significantly impacted by the distress factors. The findings are particularly useful for the teachers and institutions working to connect and teach through online platforms.